The Impact of Financial Performance, Financial Risk, Liquidity, and Corporate Governance on Corporate Value - Yunita Karlina; Andreas Lako (Soegijapranata Catholic University, 2020)
The purpose of this study is to analyze the impact of financial performance, financial risk, liquidity, and corporate governance (CG) on the corporate value in the period t0 and t+1. The proxy for financial performance, financial risk, liquidity, and corporate governance is respectively return on equity (ROE), debt to assets ratio (DAR), current ratio (CR), and corporate governance perception index (CGPI). The proxy for corporate value is price to book value (PBV). The method for analysis data is multiple linear regression analysis. The results show that financial performance has positive impact on the corporate value in the period t0 and t+1 on one percent level of significance. However, financial risk and liquidity have positive impact on the corporate value in the period t0 and t+1 but the impact is not statistically significant. CG shows different impact on the corporate value in the period t0 and t+1 in which it indicates negative impact in the period t0 but positive impact in the periode t+1. The impacts are however statistically insignificant. Generally, the results indicate that financial performance is the main factor that increases corporate value.